Journey From Garbage to Arts: The Impacts of Environmental Pollution on Living Things Are Illuminated with Eco-Art Practices - Eguz, Sule; Kocoglu, Erol; Marsak, Emine Erdogan (Sage Publications Inc, 2025)
Any damage to the planet has an irreversible impact on all humans and all life forms. This study explores the irreversible effects of environmental pollution on living organisms through an eco-art project involving undergraduate students. Using an art-based research approach, students created eco-artworks to highlight environmental issues and share their insights. Key findings reveal the effects of pollution on human health, biodiversity loss, and the habitats of land and marine species.
Keywords: eco-art project; environmental pollution; human life; living things; art-based research